A pilot study to determine the timing and effect of bevacizumab on vascular normalization of metastatic brain tumors in breast cancer. Issue 1 (December 2016) - Chen, Bang-Bin; Lu, Yen-Shen; Lin, Ching-Hung; Chen, Wei-Wu; Wu, Pei-Fang; Hsu, Chao-Yu; Yu, Chih-Wei; Wei, Shwu-Yuan; Cheng, Ann-Lii; Shih, Tiffany
Abstract Background To determine the appropriate time of concomitant chemotherapy administration after antiangiogenic treatment, we investigated the timing and effect of bevacizumab administration on vascular normalization of metastatic brain tumors in breast cancer patients. Methods Eight patients who participated in a phase II trial for breast cancer-induced refractory brain metastases were enrolled and subjected to 4 dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) examinations that evaluatedPeak, Slope, iAUC 60, andKtrans before and after treatment. The treatment comprised bevacizumab on Day 1, etoposide on Days 2–4, and cisplatin on Day 2 in a 21-day cycle for a maximum of 6 cycles. DCE-MRI was performed before treatment and at 1 h, 24 h, and 21 days after bevacizumab administration. Results Values of the 4 DCE-MRI parameters reduced after bevacizumab administration. Compared with baseline values, the mean reductions at 1 and 24 h were −12.8 and −24.7 % forPeak, −46.6 and −65.8 % forSlope, −27.9 and −55.5 % foriAUC 60, and −46.6 and −63.9 % forKtrans, respectively (allP  < .05). The differences in the 1 and 24 h mean reductions were significant (allP  < .05) for all the parameters. The generalized estimating equation linear regression analyses of the 4 DCE-MRI parameters revealed that vascular normalization peaked 24 h after bevacizumab administration. Conclusion Bevacizumab induced vascular normalization of brain metastases in humans at 1 and 24 h after administration, and the effect was significantly higher at 24 h than at 1 h. Trial registration ClinicalTrials.gov, identifierNCT01281696, registered prospectively on December 24, 2010